1983
DOI: 10.1161/01.atv.3.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat saturation and hepatic acylcoenzyme A:cholesterol acyltransferase activity. Effect of n-3 polyunsaturated and long-chain saturated fat.

Abstract: The acylcoenzyme A:cholesterol acyltransferase (ACAT) activity in liver microsomes from rats fed a diet containing 14% menhaden oil (M p ) for 11 days was 117% higher than that in microsomes from rats fed a corresponding diet containing 14% cocoa butter (M s ). There were no differences in the cholesterol and phospholipid contents of M p and M s or in the activities of palmitoyl coenzyme A hydrolase and NADPH cytochrome c reductase. NADPH-dependent lipid peroxidation was higher in M p , whereas glucose 6-phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Inclusion of 2 % cholesterol in the fish-oil diet, however, had no effect on A6desaturase activity or the C20 4,,,6-fatty-acid content of liver microsomes. It has been recently demonstrated that the rate ofcholesterol ester formation by liver microsomal acyl-CoA: cholesterol acyltransferase is accelerated by supplementing the rat diet with fish oil (rich in C20:5 and C22:6,.3 fatty acids) [38,39]. This would mean that C20:50:,3 and/or C22:60,3 fatty acids, instead of C20:4,.6 fatty acid, are utilized for cholesterol esterification in animals fed on a fish-oil-supplemented diet and that C20:5,,.3 and C22:6,.3 fatty acids are readily available for increased demand in utilization caused by 2 % cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of 2 % cholesterol in the fish-oil diet, however, had no effect on A6desaturase activity or the C20 4,,,6-fatty-acid content of liver microsomes. It has been recently demonstrated that the rate ofcholesterol ester formation by liver microsomal acyl-CoA: cholesterol acyltransferase is accelerated by supplementing the rat diet with fish oil (rich in C20:5 and C22:6,.3 fatty acids) [38,39]. This would mean that C20:50:,3 and/or C22:60,3 fatty acids, instead of C20:4,.6 fatty acid, are utilized for cholesterol esterification in animals fed on a fish-oil-supplemented diet and that C20:5,,.3 and C22:6,.3 fatty acids are readily available for increased demand in utilization caused by 2 % cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…A menhaden oil containing more than 17% of PUFA n-3 produced lower liver cholesterol content than oleic acid (Mohamed et al, 2002). Several authors have found the enzyme acyl-CoA : cholesterol acyltransferase (ACAT) is stimulated by diets enriched with PUFA n-3, a situation that in turn explains the increase of cholesterol ester pool found for several authors in this organ (Spector et al, 1980;Johnson et al, 1983;Field et al, 1987;Parks and Bullock, 1987). However, in all these studies the effects of PUFA n-3 Table 3.…”
Section: Liver Weight and Liver Compositionmentioning
confidence: 97%